Cold‐induced vasodilation in abstinent smokers with and without a 12‐hour nicotine patch. (29th April 2021) - Lee, Kichang; Cheatham, Christopher C.; Mack, Gary W.
Abstract: This study was designed to identify the effects of a 12‐h nicotine patch administration on cold induced vasodilation (CIVD) in healthy young chronic smokers following 16 h of abstinence from smoking. Two laser Doppler probes and temperature thermocouples were placed on the dorsal part of the distal phalanx of the middle and ring fingers of 7 smokers (>12 cigarettes/day). Following 16 h of abstinence from smoking, smokers were tested with and without administration of a 21 mg transdermal nicotine patch (NicoDerm ® ). Each participant's right hand was immersed in cold (~5°C) water for 40 min. Cutaneous vascular conductance (CVC) was calculated from non‐invasive arterial finger blood pressure and skin blood flow and expressed as a percentage of peak CVC observed during hand skin heating to 44°C. For comparison purposes, the CIVD response of a non‐smoking cohort without nicotine patch ( n = 10) was also examined. Baseline CVC was similar in smokers and non‐smokers (27.8 ± 12.6 CVC % peak). The initial vasoconstriction during cold‐water immersion decreased skin blood flow to 4.0 ± 3.9 CVC % peak in both smokers and non‐smokers. The onset of CIVD in smokers (4.5 ± 1.5 min) was delayed compared to non‐smoker (3.3 ± 0.8 min, p < .05). The area under the CVC %peak‐time curve during cold‐water immersion averaged 1250 ± 388 CVC %peak · min in non‐smokers which was larger ( p < .05) than smokers with or without nicotine (789 ± 542 and 862 ± 517 CVC %peak · min, respectively). Chronic smoking impaired the CIVD response to cold‐water immersion of the hand; however, the impaired CIVD response in 16 h of abstinence from smoking was not influenced by application of a 21 mg transdermal nicotine patch.